The HrpZ proteins of Pseudomonas syringae pvs. syringae, glycinea, and tomato are encoded by an operon containing Yersinia ysc homologs and elicit the hypersensitive response in tomato but not soybean. - Preston, G; Huang, H; He, S; Collmer, A (1995)
The Pseudomonas syringae pathovars are composed of host-specific plant pathogens that characteristically elicit the defense-associated hypersensitive response (HR) in nonhost plants. P. s. pv. syringae 61 secretes an HR elicitor, harpinPss (HrpZPss), in a hrp-dependent manner. An internal fragment of the P. s. pv. syringae 61 hrpZ gene was used to clone the hrpZ locus from P. s. pv. glycinea race 4 (bacterial blight of soybean) and P. s. pv. tomato DC3000 (bacterial speck of tomato). DNA sequence analysis revealed that hrpZ is the second ORF in a polycistronic operon. The amino acid sequence identities of HrpZPss/HrpZPsg and HrpZPss/HrpZPst were 79 and 63%, respectively. Although none of the HrpZ proteins showed significant overall sequence similarity with other known proteins, HrpZPst contained a 24-amino acid sequence that is homologous with a region of the PopA1 elicitor protein of the tomato pathogen, Pseudomonas solanacearum GMI1000. hrpA, the upstream ORF, was highly divergent: The amino acid sequence identities of HrpAPss/HrpAPsg and HrpAPss/HrpAPst were 91 and 28%, respectively, and no HrpA sequence showed similarity to known proteins. In contrast, the predicted products of the downstream ORFs in P. s. pv. syringae and P. s. pv. tomato, hrpB, hrpC, hrpD, and hrpE showed varying levels of similarity to those of yscI, yscJ, yscK, and yscL. These are colinearly arranged genes in the virC locus of Yersinia spp., which are involved in the secretion of the Yop virulence proteins via the type III pathway. The similarity of the Ysc proteins was generally stronger in comparisons with the P. s. pv. tomato Hrp proteins.(ABSTRACT TRUNCATED AT 250 WORDS)